The impact of digital banking adoption, risk management and balanced scorecard on bank’s performance / Tedhi Irawan, Che Ruhana Isa and Ervina Alfan - Irawan, Tedhi; Isa, Che Ruhana; Alfan, Ervina (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This research explores the impact of three independent variables to obtain maximum performance on bank. Depending on qualitative methodology and analytical review, the discussion of this research is developed. These approaches are considered suitable and pragmatic for the suggested model of bank’s performance. Here, the mediating role of balanced scorecard implementation on digital banking adoption and risk management towards bank’s performance were also discussed. This article proposes a performance model of bank that combines with mentioned three independent variables and bank’s performance as dependent variable. This study expects to enrich the literatures on bank’s performance specifically on digital banking adoption, risk management and balanced scorecard. In regards to practical implications, this study also attempts to provide insight for practitioners in bank industry to considers this article in order to improve the performance of their institution